KUALITAS VISUM ET REPERTUM PERLUKAAN DI RSUD ARIFIN ACHMAD PEKANBARU PERIODE 1 JANUARI 2009 - 31 DESEMBER 2013 - Rieskariesha Kiswara; Dedi Afandi; Laode Burhanuddin Mursali (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTThe most frequent Visum et repertum (VeR) requested by investigators isVeR of injury. It is because 50-70% of cases that come to the Emergency Unit areinjury cases. A good quality of VeR is required in view of its important role inlitigation of a criminal offense. This study was aimed to understand the quality ofVeR of injury in Pekanbaru Arifin Achmad General Hospital during 1 January2009-31 December 2013. The research was an observational study usingdescriptive retrospective design. This study used Herkutanto’s scoring methodtowards 13 VeR substances. Samples of this study were all data of VeR of injurythat had fulfilled inclusion criteria. The total of samples were 150 samples of VeR.This study suggested that the highest number of living victims of injury cases was61 victims (40,7%) in age group 22-40 years old with the most frequent sex wasmale as many as 120 victims (80%). The most frequent violence was bluntviolence as many as 125 (83,3%) cases with the most frequent age group was 22-40 years old. The quality of VeR in preface was 54,47% (medium), in body partwas 46,22% (poor) and in conclusion was 30,33% (poor). In general, quality ofVeR of injury in Pekanbaru Arifin Achmad General Hospital during 1 january2009-31 december 2013 was 37,75% that could be categorized as poor quality.Keywords: Visum et Repertum, injury, quality of VeR of injury